SYNCHRONIZATION OF EVENT-DRIVEN MANAGEMENT DURING DATA COLLECTION - Kuzminykh, Valeriy; Koval, Oleksandr; Havrylko, Yevhen; Xu, Beibei; Yepifanova, Iryna; Zhu, Shiwei; Bieliaieva, Nataliia; Yeraliyeva, Bakhyt (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article considers an approach to implementing the architecture of a microservice system for processing large volumes of data based on the event-oriented approach to managing the sequence of using individual microservices. This becomes especially important when processing large volumes of data from information sources with different performance levels when the task is to minimize the total time for processing data streams. In this case, as a rule, the task is to minimize the number of requests for information sources to obtain a sufficient amount of data relevant to the request. The efficiency of the entire software system as a whole depends on how the microservices that provide extraction and primary processing of the received data are managed. To obtain the required amount of relevant data from diverse information sources, the software system must adapt to the request during its operation so that the maximum number of requests are directed to sources that have the maximum probability of finding the data necessary for the request in them. An approach is proposed that allows adaptively managing the choice of microservices during data collection and by emerging events and, thus, forming a choice of information sources based on an assessment of the efficiency of obtaining relevant information from these sources. Events are generated as a result of data extraction and primary processing from certain sources in terms of assessing the availability of data relevant to the request in each of the sources considered within the framework of the selected search scenario. Event-oriented microservice architecture adapts the system operation to the current loads on individual microservices and the overall performance by analyse the relevant events. The use of an adaptive event-oriented microservice architecture can be especially effective in the development of various information and analytical systems constructed by real-time data collection and design scenarios of analytical activity. The article considers the features of synchronous and asynchronous options in the implementation of event-oriented architecture, which can be used in various software systems depending on their purpose. An analysis of the features of synchronous and asynchronous options in the implementation of event-oriented architecture, their quantitative parameters, and features of their use depending on the type of tasks is carried out.